For all the saints evangelical theology and Christian spirituality - George, Timothy; McGrath, Alister Edgar, 1953- (Louisville, KE Westminster/John Knox, 2003)
Includes bibliographical references and index.
Keywords: Evangelicalism -- theology -- congresses; Spirituality -- congresses